Complementary and Alternative Medicine Use at a Comprehensive Cancer Center. (March 2017) - Luo, Qianlai; Asher, Gary N.
Background . Complementary and alternative medicine (CAM) use is common among cancer patients, but the majority of CAM studies do not specify the time periods in relation to cancer diagnoses. We sought to define CAM use by cancer patients and investigate factors that might influence changes in CAM use in relation to cancer diagnoses. Methods . We conducted a cross-sectional survey of adults diagnosed with breast, prostate, lung, or colorectal cancer between 2010 and 2012 at the Lineberger Comprehensive Cancer Center. Questionnaires were sent to 1794 patients. Phone calls were made to nonrespondents. Log binomial/Poisson regressions were used to investigate the association between cancer-related changes in CAM use and conversations about CAM use with oncology providers. Results . We received 603 (33.6 %) completed questionnaires. The mean age (SD) was 64 (11) years; 62% were female; 79% were white; and 98% were non-Hispanic. Respondents reported the following cancer types: breast (47%), prostate (27%), colorectal (14%), lung (11%). Eighty-nine percent reported lifetime CAM use. Eighty-five percent reported CAM use during or after initial cancer treatment, with category-specific use as follows: mind-body medicine 39%, dietary supplements 73%, body-based therapies 30%, and energy medicine 49%. During treatment CAM use decreased for all categories except energy medicine. After treatment CAM use returned to pretreatment levels for most CAMs except chiropractic. Initiation of CAM use after cancer diagnosis was positively associated with a patient having a conversation about CAM use with their oncology provider, mainly driven by patient-initiated conversations. Conclusions . Consistent with previous studies, CAM use was common among our study population. Conversations about CAM use with oncology providers appeared to influence cessation of mind-body medicine use after cancer diagnosis.